Beliefs in teaching grammar and common classroom practices in schools in Malaysia - Nurusus, Elisha (2016)
This study looked at the teachers’ beliefs using the data collected from a survey conducted on 345 English Language teachers teaching in secondary schools from state of Melaka and Perak in Malaysia. Teachers’ beliefs play a crucial role in teachers’ decision-making process regarding the type of materials, activities and instruction they use in their lessons. A teacher’s belief on how their learners should learn also instrumental in ensuring the effectiveness of their teaching regardless of the approach they take. Every teacher own a set of personal beliefs regarding the teaching of grammar and how grammar should be taught to the learners. The teachers’ years of experience in teaching, their academic background and the location of the school can easily shape teachers’ beliefs about grammar teaching. The sample was decided using cluster sampling and Cochran formula of sampling was used to determine the sample size. The instrument for the study is self-developed questionnaire, modeled after the computational model of second language acquisition by Ellis (1998). The items in the questionnaire pertaining teachers’ beliefs were measured using 5-point Likert scale, ranging from 1, Strongly Disagree to 5, Strongly Agree. The instrument pinpoint four aspects of grammar instruction in the classroom that English Language teachers can use – Input, Elicit L2 Knowledge, student Output and Feedback or error correction. One of the aims of the study is to find out what is the most subscribed belief that the participating English Language teachers have. The study also looked into how teachers of different years of teaching experience viewed the importance of the four aspects of grammar instruction. Analysis also done to look at the importance of each of the four aspects of grammar teaching instruction according to Ellis (1998) by the teachers’ years of experience, academic background and school location were also looked into. The teachers’ common classroom practices when they are teaching grammar in the classroom was also identified. The results indicated that a large number of teachers involved in this study believe that Feedback is the most important teaching instruction in grammar teaching. The repeated measures ANOVA results indicate an interesting pattern where the teachers with more than 30 years of experience (F, 13.97, p<0.5) placed more importance on providing Feedback. The teachers with less than 7 years of experience (F, 13.74, p<0.5) placed more importance on Output. The pairwise comparison for teachers’ academic background indicates that teachers with TESL background have more preference for Feedback (27.95) and L2 Knowledge (25.20). The result also shows that teachers without TESL background prefer Feedback (28.80). The pairwise comparisons for teachers in urban locations showed significant values between Feedback and all the other emphases with Wilks’ Lambda = .732, F (3, 165) = 20.18, p< .05. There are significant differences in all pairwise comparisons except between Output and Input for teachers in rural locations with Lambda = .546, F (3, 146) = 40.45, p < .05. The common classroom practices among teachers who subscribed to Feedback, Output and Input is to frequently use Practice 3 which is correcting students' grammatical errors in the class. Meanwhile, teachers who subscribed to Explicit L2 Knowledge found to be frequently use Practice 2, providing as many examples as possible of the grammar structures. The study discussed the implications and effects of the results and findings from this study on the stakeholders and future research.